The Influence of Work Behavior on Employee Performance Mediated by Organizational Commitment, in Tungwatu Village Officials, Pulau Aru District - Tiwery, Leonora; Latupapua , Conchita V; Lewaherilla, Novalien (Jurnal Ekonomi, 2024)
The aim of this research is to analyze the influenceWork Behavior on Employee Performance Mediated by Organizational Commitment, in Tungwatu Village Officials, Pulau Aru District. This research is quantitative descriptive research. The population in this study was Tungwatu Village Officials, Pulau Aru District, totaling 30 respondents. By using a questionnaire. Sampling usingSampling used a non-probability sampling technique with a purposive sampling method. The data analysis method used is SEM PLS to test the formative and reflective models between indicators. Based on the results of the data tests that have been carried out, it shows that the variableWork Behavior(X1) has a positive and significant influence on performance (Y) as a mediating variable and organizational commitment variable (Z). Likewise, it has a positive and significant influence on performance (Y) as a mediating variable and organizational commitment variable (Z). The research results also show that work behavior has a very high influence on employee performance and organizational commitment. This shows that work behavior is still dominated by organizational commitment or references from other people who have organizational commitment.